2016
DOI: 10.1016/j.jcyt.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Scalability and process transfer of mesenchymal stromal cell production from monolayer to microcarrier culture using human platelet lysate

Abstract: This study has demonstrated that HPL, compared with FBS-containing medium, delivers increased growth and comparability across two BM-hMSC donors between monolayer and microcarrier culture, which will have key implications for process transfer during scale-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
4
38
0
Order By: Relevance
“…These findings are in line with previously published articles for both microcarrier and monolayer culture [26,27].…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…These findings are in line with previously published articles for both microcarrier and monolayer culture [26,27].…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…Mechanical stimuli such as stretch, strain‐induced oscillatory fluid flow, hydrodynamic stress, and low‐dose ionizing radiation have also been demonstrated to enhance MSC proliferation . Even in dynamic cell culture systems such as spinner flasks and stirred‐tank bioreactors which are used for large‐scale in‐vitro expansion of these cells, the improvement in cell yield were noticed mainly due to increased surface area rather than any improvement in the proliferation capacity of the cells as similar specific growth rates were observed between static and dynamic culture conditions . While activation of either MAPK/ERK pathway, ATP release or Ca 2+ signaling have been implicated in the response of MSCs to mechanical stimuli, the molecular mechanisms that selectively couple the external stimuli to the cellular machinery, which controls MSC proliferation remains poorly understood .…”
Section: Introductionmentioning
confidence: 99%
“…[7,[10][11][12][13] Even in dynamic cell culture systems such as spinner flasks and stirred-tank bioreactors which are used for large-scale in-vitro expansion of these cells, the improvement in cell yield were noticed mainly due to increased surface area rather than any improvement in the proliferation capacity of the cells as similar specific growth rates were observed between static and dynamic culture conditions. [14][15][16][17] While activation of either MAPK/ERK pathway, ATP release or Ca 2þ signaling have been implicated in the response of MSCs to mechanical stimuli, the molecular mechanisms that selectively couple the external stimuli to the cellular machinery, which controls MSC proliferation remains poorly understood. [7,[10][11][12] This comprehensive knowledge may prove useful in several practical applications, such as in the design of bioreactors for the efficient in vitro expansion of MSCs or treatment strategies that aim to recruit MSCs from in vivo niches to facilitate tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest reported study for HPL‐based MSC expansion in a bioreactor system was carried out by Petry et al in 2015 wherein UCB MSCs were expanded using 10% HPL supplemented medium, on microcarriers in spinner flasks . Heathman et al also demonstrated in 2016 that the use of HPL in microcarrier‐based spinner flask culture of BM MSCs resulted in a smaller lag phase and increased yield in comparison to FBS. They further showed that the use of HPL increased interdonor consistency contributing to robust bioprocess outcomes and hence aiding the use of MSCs in clinical settings.…”
Section: Introductionmentioning
confidence: 99%